Factors Influencing Online Shopping Behavior Focusing on LAZADA, SHOPPEE and JD - Wongsunopparat, Sumas; Yunjia, Zhang (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study examines the factors influencing online shopping behavior focusing on LAZADA, SHOPPEE and JD. For this purpose, the analysis is conducted with 400 people who prefer different types of online shopping platform by utilizing structural equation modeling (SEM). Six potential influencing factors on consumer online platform choice are brand effect, product offering, platform feature, special offer and shopping safety. The result shows that the model’s chi-square value of 285.739 with 263 degrees of freedom is non-significant at the .05 level which suggests that model fits the data acceptably in the population from which we drew our sample. Corroborating evidence is provided by the RMSEA fit statistic – the obtained value of .014 is well below the desired .06 cutoff. Similarly, the Tucker-Lewis Index (TLI) result of .998 as well as GFI (.952) and CFI (.998) are considerably above the .95 threshold denoting satisfactory model fit. Therefore, our proposed SEM model seems to fit well according to the descriptive measures of fit. More importantly, Platform (PF) and Brand (BE) seem to have significant effects on online-shopping behavior due to their p-values are both less than .05. This research is significant because it makes it possible for operators to understand how to influence user’s online shopping platform choice decision, which is important for establishing relevant strategies.